Method for solving deformation of single-sided marble battery rear cover
During the manufacturing process of the battery back cover, high-density fiber and glass fiber are prepreged with epoxy resin, combined with the marble surface, and the prepreg material is successively superimposed, and the hot press forming process is adopted to solve the problem of deformation of the back cover of the single-sided marble battery, achieving an efficient and stable production process.
Patent Information
- Application Number
- CN202510158581.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-13
- Publication Date
- 2025-04-25
AI Technical Summary
The back cover of the single-sided marble battery is prone to deformation problems after hot pressing, resulting in aesthetic damage to the appearance and the assembly accuracy not meeting the standards. The existing technology relies on manual plastic surgery but has high cost and unstable effect.
By pre-soaking high-density fibers and glass fibers with epoxy resin, semi-curing, combining three layers of pre-soaked glass fibers and one layer of high-density fibers on the marble surface in turn, the battery back cover is prepared by using hot pressing molding process, and the stresses of high-density fibers and marble are offset by mutual stress balance to achieve internal stress balance.
It effectively solves the problem of battery back cover deformation, reduces the demand for manual plastic surgery, reduces production costs and working hours, and improves product stability and yield.
Smart Images

Figure CN119871939A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery back covers, and in particular to a method for solving the deformation of a single-sided marble battery back cover. Background Art
[0002] Marble battery cover is a new type of battery cover material that combines the decorative effect of marble texture with the high strength and lightness of glass fiber material. This battery cover is usually used in high-end electronic products such as smart phones, tablets, etc. Its design not only improves the appearance and texture of the product, but also enhances the structural strength and anti-fall performance.
[0003] In the manufacturing process, a key step is hot pressing, which requires that the pre-stacked multi-layer materials are neatly placed into the mold cavity, and then the high temperature and high pressure are used to make them tightly combine and form the final product. However, in actual operation, the products after hot pressing often have deformation problems to varying degrees. This deformation may be caused by uneven expansion or contraction of the material during heating and pressure, or it may be due to insufficient adhesion between the stacked materials, resulting in relative displacement between the layers during the molding process. Deformed products not only affect the appearance, but more importantly, they often cannot meet the precision requirements of subsequent assembly processes.
[0004] To solve this problem, existing technologies have adopted a manual intervention method. After hot pressing, workers need to check and reshape the deformed products one by one to ensure that they meet the subsequent assembly standards. However, this manual shaping method not only greatly increases production costs and working hours, but the shaping effect is often limited by the skills and experience of the operator, and it is difficult to ensure the consistency and stability of the product. In addition, manual shaping may also cause additional difficulties for the subsequent assembly. Since the shaped products may have slight size differences or irregular shapes, this may lead to poor coordination with other components during the assembly process, which in turn affects the installation effect and final quality of the entire product, and greatly reduces the product yield.
[0005] In summary, in order to solve the above problems, it is of great significance to provide a method for solving the deformation of the back cover of a single-sided marble battery. Summary of the invention
[0006] The purpose of the present invention is to provide a method for solving the deformation of the back cover of a single-sided marble battery, so as to solve the problems raised in the prior art.
[0007] To achieve the above object, the present invention provides the following technical solutions: A method for solving the deformation of a single-sided marble battery back cover, specifically comprising the following steps: S1: immersing the high-density fiber in epoxy resin glue, taking it out, semi-curing it, and obtaining pre-impregnated high-density fiber; S2: immersing the glass fiber in epoxy resin glue, taking it out, semi-curing it, and obtaining pre-impregnated glass fiber; S3: Three layers of pre-impregnated glass fiber and one layer of pre-impregnated high-density fiber are stacked in sequence on the upper surface of the marble, transferred to a mold, and hot-pressed to obtain a marble battery back cover.
[0008] The epoxy resin glue comprises the following substances, calculated by mass: 100 parts of bisphenol A epoxy resin, 30-35 parts of 4,4'-diaminodiphenyl sulfone, 15-18 parts of phenolic resin, 8-10 parts of modified nano-calcium carbonate, 0.05-0.1 parts of azobisisobutyronitrile, and 25-30 parts of acetone.
[0009] Preferably, the epoxy resin glue has a dipping amount of 100-130 g / m 2 ; Preferably, during the semi-curing process, UV curing is performed at a temperature of 80-120°C for 30-40 minutes; during the hot pressing process, the pressure is 4-6 MPa, the temperature is 180-200°C, and the time is 2-3 hours.
[0010] Preferably, the preparation method of the phenolic resin comprises the following steps: uniformly mixing formaldehyde, phenol and 0.5-1 part of sodium carbonate, stirring at 70-75°C for 2-3h, adding 5-(4-pentene-1-oxy)pyridin-3-ylboronic acid, refluxing at 100-104°C for 3-3.5h, cooling to 75-80°C, dehydrating by reduced pressure distillation for 20-30min, adding methyltrimethoxysilane, stirring at 100-105°C for 30-40min, dehydrating by reduced pressure distillation for 20-30min, and obtaining a phenolic resin.
[0011] The phenolic resin comprises the following raw materials, calculated by mass: 14 to 16 parts of formaldehyde, 9 to 10 parts of phenol, 0.5 to 1 part of sodium carbonate, 6 to 7 parts of 5-(4-pentene-1-oxy)pyridin-3-ylboric acid, and 1 to 2 parts of methyltrimethoxysilane.
[0012] Preferably, the preparation method of the modified nano-calcium carbonate comprises the following steps: (1) drying the nano-calcium carbonate, adding it to a phosphoric acid solution, ultrasonically dispersing and stirring for 5 to 10 minutes, filtering, washing, and drying to obtain phosphoric acid-modified nano-calcium carbonate; (2) adding the phosphoric acid-modified nano-calcium carbonate to a 70 to 80% ethanol aqueous solution, ultrasonically dispersing it uniformly, adding 3-aminopropyltriethoxysilane and mercaptopropyltrimethoxysilane, and stirring at 40 to 50° C. for 6 to 7 hours to obtain modified nano-calcium carbonate.
[0013] Among them, the phosphoric acid-modified nano-calcium carbonate includes the following raw materials in parts by mass: 4 to 6 parts of nano-calcium carbonate and 10 to 20 parts of 3% phosphoric acid solution; the modified nano-calcium carbonate includes the following raw materials in parts by mass: 4 to 6 parts of phosphoric acid-modified nano-calcium carbonate, 30 to 40 parts of 70 to 80% ethanol aqueous solution, 3 to 5 parts of 3-aminopropyltriethoxysilane and 2 to 3 parts of mercaptopropyltrimethoxysilane.
[0014] Compared with the prior art, the beneficial effects of this application are as follows: (1) The present invention pre-impregnates high-density fiber and glass fiber with epoxy resin, semi-cures them, obtains pre-impregnated high-density fiber and pre-impregnated glass fiber, and then uses a layer of marble as the base surface, sequentially stacks three layers of pre-impregnated glass fiber and a layer of high-density fiber, and uses a press to hot-press or autoclave to high-pressure mold to obtain the product. During the hot-press molding of marble and glass fiber, stress is generated during the flow and solidification of the resin under pressure, which causes product deformation due to the imbalance of the marble stress. Adding a layer of high-density fiber material to the glass fiber layer can well offset the marble stress, ensure the internal stress balance of the product, and thus solve the problem of product deformation. Compared with the traditional solution, the present invention replaces a layer of marble with a layer of high-density fiber at the bottom of the glass fiber stack, which helps to intuitively save the labor cost of secondary shaping and the cost of a layer of marble, shortens the process time, advances the delivery time, has a stable and high product output, a low defective rate of hot-pressed products, is easy to operate, and can completely solve the problem of deformation.
[0015] (2) The present invention introduces phenolic resin into epoxy resin. Phenolic resin can improve the strength of epoxy resin, thereby improving the mechanical properties of high-density fiber, and at the same time, it can also improve the curing characteristics of epoxy resin. By introducing 5-(4-pentene-1-oxy)pyridine-3-ylboronic acid and methyltrimethoxysilane, it can be combined with unreacted phenolic hydroxyl groups in phenolic resin for grafting, thereby reducing the phenol content in phenolic resin, and introducing silicon-oxygen-boron bonds to improve thermal stability, thereby reducing the thermal stress of epoxy resin curing and reducing the possibility of deformation.
[0016] (3) The present invention also introduces nano-calcium carbonate into the epoxy resin. The addition of nano-calcium carbonate can reduce the shrinkage rate of the epoxy resin during curing, reduce internal stress, and reduce deformation. At the same time, the present invention modifies the nano-calcium carbonate by adding phosphoric acid to react with the surface of calcium carbonate to form phosphate, which helps to improve the flame retardant properties of the phenolic resin. At the same time, aminosilane coupling agent and mercaptosilane coupling agent are used to graft and modify the surface, thereby improving the dispersibility and bonding of nano-calcium carbonate in the system. The introduced mercapto group will also click with the alkenyl group in the phenolic resin grafted with the added 5-(4-pentene-1-oxy)pyridine-3-ylboronic acid, thereby increasing the strength of the epoxy resin. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1It is a schematic diagram of the stacking of the single-sided marble battery back cover of the present invention. DETAILED DESCRIPTION
[0018] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0019] It should be noted that the purchase manufacturers of all raw materials involved in the present invention are not subject to any special restrictions, and illustratively include: formaldehyde; phenol; sodium carbonate; 5-(4-pentene-1-oxy)pyridin-3-ylboric acid, CAS No.: 1350513-05-1; methyltrimethoxysilane, CAS No.: 1185-55-3; nano calcium carbonate, with a particle size of 60-80 nm, provided by Zhejiang Tianshi Nano Technology Co., Ltd.; 3-aminopropyltriethoxysilane, CAS No.: 919-30-2; mercaptopropyltrimethoxysilane, CAS No.: 4420-74-0; bisphenol A epoxy resin (DGEBA), E51, provided by Guangzhou Yihuisheng Chemical Co., Ltd.; 4,4'-diaminodiphenyl sulfone, CAS No.: 80-08-0; the above raw materials and the raw materials not mentioned in the examples are all commercially available.
[0020] In the following examples and comparative examples, parts are by mass, and the epoxy resin glue dipping amount is 120g / m 2 .
[0021] Embodiment 1: A method for solving the deformation of the rear cover of a single-sided marble battery, specifically comprising the following steps: Step 1: Preparation of phenolic resin: 15 parts of formaldehyde, 9.5 parts of phenol and 0.7 parts of sodium carbonate were mixed evenly, stirred at 75°C for 2.5 hours, 6.5 parts of 5-(4-pentene-1-oxy)pyridin-3-ylboronic acid were added, refluxed at 102°C for 3 hours, cooled to 80°C, dehydrated by vacuum distillation for 30 minutes, 1.5 parts of methyltrimethoxysilane were added, stirred at 105°C for 35 minutes, and dehydrated by vacuum distillation for 30 minutes to obtain phenolic resin; Step 2: Preparation of modified nano-calcium carbonate: (1) Dry 5 parts of nano-calcium carbonate, add to 15 parts of 3% phosphoric acid solution, ultrasonically disperse and stir for 5 minutes, filter, wash and dry to obtain phosphoric acid-modified nano-calcium carbonate; (2) Add 5 parts of phosphoric acid-modified nano-calcium carbonate to 35 parts of 75% ethanol aqueous solution, ultrasonically disperse evenly, add 4 parts of 3-aminopropyltriethoxysilane and 2.5 parts of mercaptopropyltrimethoxysilane, stir at 45°C for 6.5 hours to obtain modified nano-calcium carbonate; Step 3: Preparation of marble battery back cover: S1: immersing the high-density fiber in epoxy resin glue, taking it out, and UV curing it at 100°C for 30 minutes to obtain pre-impregnated high-density fiber; S2: immersing the glass fiber in epoxy resin glue, taking it out, and UV curing it at 100°C for 30 minutes to obtain pre-impregnated glass fiber; S3: stack three layers of pre-impregnated glass fiber and one layer of pre-impregnated high-density fiber on the upper surface of the marble, transfer them to a mold, and hot-press them at a temperature of 200°C for 3 hours under a pressure of 5 MPa to obtain a marble battery back cover; The epoxy resin glue comprises the following substances, calculated by mass: 100 parts of bisphenol A epoxy resin, 30 parts of 4,4'-diaminodiphenyl sulfone, 16 parts of phenolic resin, 9 parts of modified nano-calcium carbonate, 0.05 parts of azobisisobutyronitrile, and 26 parts of acetone.
[0022] Embodiment 2: A method for solving the deformation of the rear cover of a single-sided marble battery, specifically comprising the following steps: Step 1: Preparation of phenolic resin: 15 parts of formaldehyde, 9.5 parts of phenol and 0.7 parts of sodium carbonate were mixed evenly, stirred at 75°C for 2.5 hours, 6.5 parts of 5-(4-pentene-1-oxy)pyridin-3-ylboronic acid were added, refluxed at 102°C for 3 hours, cooled to 80°C, dehydrated by vacuum distillation for 30 minutes, 1.5 parts of methyltrimethoxysilane were added, stirred at 105°C for 35 minutes, and dehydrated by vacuum distillation for 30 minutes to obtain phenolic resin; Step 2: Preparation of modified nano-calcium carbonate: (1) Dry 5 parts of nano-calcium carbonate, add to 15 parts of 3% phosphoric acid solution, ultrasonically disperse and stir for 5 minutes, filter, wash and dry to obtain phosphoric acid-modified nano-calcium carbonate; (2) Add 5 parts of phosphoric acid-modified nano-calcium carbonate to 35 parts of 75% ethanol aqueous solution, ultrasonically disperse evenly, add 4 parts of 3-aminopropyltriethoxysilane and 2.5 parts of mercaptopropyltrimethoxysilane, stir at 45°C for 6.5 hours to obtain modified nano-calcium carbonate; Step 3: Preparation of marble battery back cover: S1: immersing the high-density fiber in epoxy resin glue, taking it out, and UV curing it at 80°C for 30 minutes to obtain pre-impregnated high-density fiber; S2: immersing the glass fiber in epoxy resin glue, taking it out, and UV curing it at 80°C for 30 minutes to obtain pre-impregnated glass fiber; S3: stack three layers of pre-impregnated glass fiber and one layer of pre-impregnated high-density fiber on the upper surface of the marble, transfer them to a mold, and hot-press them at a temperature of 180°C for 2 hours under a pressure of 4 MPa to obtain a marble battery back cover; The epoxy resin glue comprises the following substances, calculated by mass: 100 parts of bisphenol A epoxy resin, 30 parts of 4,4'-diaminodiphenyl sulfone, 15 parts of phenolic resin, 8 parts of modified nano-calcium carbonate, 0.05 parts of azobisisobutyronitrile, and 25 parts of acetone.
[0023] Embodiment 3: A method for solving the deformation of the rear cover of a single-sided marble battery, specifically comprising the following steps: Step 1: Preparation of phenolic resin: 15 parts of formaldehyde, 9.5 parts of phenol and 0.7 parts of sodium carbonate were mixed evenly, stirred at 75°C for 2.5 hours, 6.5 parts of 5-(4-pentene-1-oxy)pyridin-3-ylboronic acid were added, refluxed at 102°C for 3 hours, cooled to 80°C, dehydrated by vacuum distillation for 30 minutes, 1.5 parts of methyltrimethoxysilane were added, stirred at 105°C for 35 minutes, and dehydrated by vacuum distillation for 30 minutes to obtain phenolic resin; Step 2: Preparation of modified nano-calcium carbonate: (1) Dry 5 parts of nano-calcium carbonate, add to 15 parts of 3% phosphoric acid solution, ultrasonically disperse and stir for 5 minutes, filter, wash and dry to obtain phosphoric acid-modified nano-calcium carbonate; (2) Add 5 parts of phosphoric acid-modified nano-calcium carbonate to 35 parts of 75% ethanol aqueous solution, ultrasonically disperse evenly, add 4 parts of 3-aminopropyltriethoxysilane and 2.5 parts of mercaptopropyltrimethoxysilane, stir at 45°C for 6.5 hours to obtain modified nano-calcium carbonate; Step 3: Preparation of marble battery back cover: S1: immersing the high-density fiber in epoxy resin glue, taking it out, and UV curing it at 120°C for 40 minutes to obtain pre-impregnated high-density fiber; S2: immersing the glass fiber in epoxy resin glue, taking it out, and UV curing it at 120°C for 40 minutes to obtain pre-impregnated glass fiber; S3: stack three layers of pre-impregnated glass fiber and one layer of pre-impregnated high-density fiber on the upper surface of the marble, transfer them to the mold, and hot press them at a temperature of 200°C for 3 hours under a pressure of 6 MPa to obtain a marble battery back cover; The epoxy resin glue comprises the following substances, calculated by mass: 100 parts of bisphenol A epoxy resin, 35 parts of 4,4'-diaminodiphenyl sulfone, 18 parts of phenolic resin, 10 parts of modified nano-calcium carbonate, 0.1 parts of azobisisobutyronitrile, and 30 parts of acetone.
[0024] Comparative Example 1: Based on Example 1, no phenolic resin is added to the epoxy resin, and the other processes remain unchanged, as follows: Step 1: Preparation of modified nano-calcium carbonate: (1) Dry 5 parts of nano-calcium carbonate, add to 15 parts of 3% phosphoric acid solution, ultrasonically disperse and stir for 5 minutes, filter, wash and dry to obtain phosphoric acid-modified nano-calcium carbonate; (2) Add 5 parts of phosphoric acid-modified nano-calcium carbonate to 35 parts of 75% ethanol aqueous solution, ultrasonically disperse evenly, add 4 parts of 3-aminopropyltriethoxysilane and 2.5 parts of mercaptopropyltrimethoxysilane, stir at 45°C for 6.5 hours to obtain modified nano-calcium carbonate; Step 2: Preparation of marble battery back cover: S1: immersing the high-density fiber in epoxy resin glue, taking it out, and UV curing it at 100°C for 30 minutes to obtain pre-impregnated high-density fiber; S2: immersing the glass fiber in epoxy resin glue, taking it out, and UV curing it at 100°C for 30 minutes to obtain pre-impregnated glass fiber; S3: stack three layers of pre-impregnated glass fiber and one layer of pre-impregnated high-density fiber on the upper surface of the marble, transfer them to a mold, and hot-press them at a temperature of 200°C for 3 hours under a pressure of 5 MPa to obtain a marble battery back cover; The epoxy resin glue comprises the following substances, calculated by mass: 100 parts of bisphenol A epoxy resin, 46 parts of 4,4'-diaminodiphenyl sulfone, 9 parts of modified nano-calcium carbonate, 0.05 parts of azobisisobutyronitrile, and 26 parts of acetone.
[0025] Comparative Example 2: Based on Example 1, the epoxy resin is not added with modified nano calcium carbonate, and the other processes remain unchanged, as follows: Step 1: Preparation of phenolic resin: 15 parts of formaldehyde, 9.5 parts of phenol and 0.7 parts of sodium carbonate were mixed evenly, stirred at 75°C for 2.5 hours, 6.5 parts of 5-(4-pentene-1-oxy)pyridin-3-ylboronic acid were added, refluxed at 102°C for 3 hours, cooled to 80°C, dehydrated by vacuum distillation for 30 minutes, 1.5 parts of methyltrimethoxysilane were added, stirred at 105°C for 35 minutes, and dehydrated by vacuum distillation for 30 minutes to obtain phenolic resin; Step 2: Preparation of marble battery back cover: S1: immersing the high-density fiber in epoxy resin glue, taking it out, and UV curing it at 100°C for 30 minutes to obtain pre-impregnated high-density fiber; S2: immersing the glass fiber in epoxy resin glue, taking it out, and UV curing it at 100°C for 30 minutes to obtain pre-impregnated glass fiber; S3: stack three layers of pre-impregnated glass fiber and one layer of pre-impregnated high-density fiber on the upper surface of the marble, transfer them to a mold, and hot-press them at a temperature of 200°C for 3 hours under a pressure of 5 MPa to obtain a marble battery back cover; The epoxy resin glue comprises the following substances, calculated by mass: 100 parts of bisphenol A epoxy resin, 39 parts of 4,4'-diaminodiphenyl sulfone, 16 parts of phenolic resin, 0.05 parts of azobisisobutyronitrile, and 26 parts of acetone.
[0026] Comparative Example 3: Based on Example 1, commercially available phenolic resin was directly added to the epoxy resin, and the rest of the process remained unchanged, as follows: Step 1: Preparation of modified nano-calcium carbonate: (1) Dry 5 parts of nano-calcium carbonate, add to 15 parts of 3% phosphoric acid solution, ultrasonically disperse and stir for 5 minutes, filter, wash and dry to obtain phosphoric acid-modified nano-calcium carbonate; (2) Add 5 parts of phosphoric acid-modified nano-calcium carbonate to 35 parts of 75% ethanol aqueous solution, ultrasonically disperse evenly, add 4 parts of 3-aminopropyltriethoxysilane and 2.5 parts of mercaptopropyltrimethoxysilane, stir at 45°C for 6.5 hours to obtain modified nano-calcium carbonate; Step 2: Preparation of marble battery back cover: S1: immersing the high-density fiber in epoxy resin glue, taking it out, and UV curing it at 100°C for 30 minutes to obtain pre-impregnated high-density fiber; S2: immersing the glass fiber in epoxy resin glue, taking it out, and UV curing it at 100°C for 30 minutes to obtain pre-impregnated glass fiber; S3: stack three layers of pre-impregnated glass fiber and one layer of pre-impregnated high-density fiber on the upper surface of the marble, transfer them to a mold, and hot-press them at a temperature of 200°C for 3 hours under a pressure of 5 MPa to obtain a marble battery back cover; The epoxy resin glue comprises the following substances, calculated by mass: 100 parts of bisphenol A epoxy resin, 30 parts of 4,4'-diaminodiphenyl sulfone, 16 parts of commercially available phenolic resin, 9 parts of modified nano-calcium carbonate, 0.05 parts of azobisisobutyronitrile, and 26 parts of acetone.
[0027] Comparative Example 4: Based on Example 1, phenolic resin and modified nano calcium carbonate were not added, and the other processes remained unchanged, as follows: Step 1: Preparation of marble battery back cover: S1: immersing the high-density fiber in epoxy resin glue, taking it out, and UV curing it at 100°C for 30 minutes to obtain pre-impregnated high-density fiber; S2: immersing the glass fiber in epoxy resin glue, taking it out, and UV curing it at 100°C for 30 minutes to obtain pre-impregnated glass fiber; S3: stack three layers of pre-impregnated glass fiber and one layer of pre-impregnated high-density fiber on the upper surface of the marble, transfer them to a mold, and hot-press them at a temperature of 200°C for 3 hours under a pressure of 5 MPa to obtain a marble battery back cover; The epoxy resin glue comprises the following substances, calculated by mass: 100 parts of bisphenol A epoxy resin, 55 parts of 4,4'-diaminodiphenyl sulfone, 0.05 parts of azobisisobutyronitrile, and 26 parts of acetone.
[0028] Performance test: (1) According to GB / T 9341-2008, the bending strength of each embodiment and comparative example sample was measured by the three-point bending method on a universal testing machine, wherein the marble layer of the sample was removed before testing, and the experimental data are shown in Table 1; (2) According to GB / T 2406.2-2009, the limiting oxygen index of each embodiment and comparative example sample was measured, and the experimental data are shown in Table 1; (3) The lamination method of Example 1 and the conventional lamination scheme were used for preparation, and the conventional lamination scheme was as follows: from bottom to top, marble layer, three glass fiber layers, marble layer, and the rest was the same as Example 1; 100 mobile phone cases were prepared by each method, and the yield rate was calculated. The experimental data are shown in Table 2.
[0029] Table 1 project Bending strength / MPa LOI / % Example 1 1453 29.8 Example 2 1435 29.4 Example 3 1450 29.0 Comparative Example 1 1265 28.2 Comparative Example 2 1398 26.4 Comparative Example 3 1354 27.5 Comparative Example 4 1225 25.8 Table 2 project Yield / % Example 1 98 Conventional solution 85 Conclusion: As shown in Table 1, in Comparative Example 1, no phenolic resin is added to the epoxy resin, and the mechanical properties are reduced, the tensile strength is reduced, the thermal stability is reduced, and the limiting oxygen index is reduced; in Comparative Example 2, no modified nano-calcium carbonate is added to the epoxy resin, and the mechanical properties are reduced, and the limiting oxygen index is reduced more; in Comparative Example 3, commercially available phenolic resin is directly added to the epoxy resin, and the thermal stability is reduced, and the limiting oxygen index is reduced; in Comparative Example 4, no phenolic resin and modified nano-calcium carbonate are added to the epoxy resin, and compared with Example 1, the tensile strength and the limiting oxygen index are greatly reduced; As shown in Table 2, by replacing a marble layer with a high-density fiber according to the present invention, the yield rate is greatly reduced.
[0030] In summary, the present invention successfully provides a method for solving the deformation of the back cover of a single-sided marble battery by replacing a layer of marble with high-density fiber and adding phenolic resin and modified nano-calcium carbonate into the epoxy resin for hot pressing and curing. The method has a high yield rate and good bending strength and flame retardancy.
[0031] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for solving the deformation of the rear cover of a single-sided marble battery, characterized in that: The specific steps include: S1: immersing the high-density fiber in epoxy resin glue, taking it out, semi-curing it, and obtaining pre-impregnated high-density fiber; S2: immersing the glass fiber in epoxy resin glue, taking it out, semi-curing it, and obtaining pre-impregnated glass fiber; S3: Three layers of pre-impregnated glass fiber and one layer of pre-impregnated high-density fiber are stacked in sequence on the upper surface of the marble, transferred to a mold, and hot-pressed to obtain a marble battery back cover.
2. A method for solving the deformation of a single-sided marble battery back cover according to claim 1, characterized in that: The epoxy resin glue comprises the following substances, calculated by mass: 100 parts of bisphenol A epoxy resin, 30-35 parts of 4,4'-diaminodiphenyl sulfone, 15-18 parts of phenolic resin, 8-10 parts of modified nano calcium carbonate, 0.05-0.1 parts of azobisisobutyronitrile, and 25-30 parts of acetone.
3. The method for solving the deformation of the single-sided marble battery back cover according to claim 1, characterized in that: The epoxy resin glue has a dipping amount of 100-130 g / m 2 .
4. The method for solving the deformation of the single-sided marble battery back cover according to claim 1, characterized in that: During the semi-curing process, the UV curing is performed at a temperature of 80-120° C. for 30-40 minutes; during the hot pressing process, the pressure is 4-6 MPa, the temperature is 180-200° C. for 2-3 hours.
5. The method for solving the deformation of the single-sided marble battery back cover according to claim 2, characterized in that: The preparation method of the phenolic resin comprises the following steps: uniformly mixing formaldehyde, phenol and 0.5-1 part of sodium carbonate, stirring at 70-75°C for 2-3h, adding 5-(4-pentene-1-oxy)pyridin-3-ylboronic acid, refluxing at 100-104°C for 3-3.5h, cooling to 75-80°C, dehydrating by reduced pressure distillation for 20-30min, adding methyltrimethoxysilane, stirring at 100-105°C for 30-40min, dehydrating by reduced pressure distillation for 20-30min, and obtaining the phenolic resin.
6. A method for solving the deformation of a single-sided marble battery back cover according to claim 5, characterized in that: The phenolic resin comprises the following raw materials, calculated by mass: 14 to 16 parts of formaldehyde, 9 to 10 parts of phenol, 0.5 to 1 part of sodium carbonate, 6 to 7 parts of 5-(4-pentene-1-oxy)pyridin-3-ylboric acid, and 1 to 2 parts of methyltrimethoxysilane.
7. The method for solving the deformation of the single-sided marble battery back cover according to claim 2, characterized in that: The preparation method of the modified nano-calcium carbonate comprises the following steps: (1) drying the nano-calcium carbonate, adding it to a phosphoric acid solution, ultrasonically dispersing and stirring for 5-10 minutes, filtering, washing and drying to obtain phosphoric acid-modified nano-calcium carbonate; (2) adding the phosphoric acid-modified nano-calcium carbonate to a 70-80% ethanol aqueous solution, ultrasonically dispersing it uniformly, adding 3-aminopropyltriethoxysilane and mercaptopropyltrimethoxysilane, and stirring at 40-50° C. for 6-7 hours to obtain the modified nano-calcium carbonate.
8. The method for solving the deformation of the single-sided marble battery back cover according to claim 7, characterized in that: The phosphoric acid-modified nano-calcium carbonate comprises the following raw materials in parts by mass: 4 to 6 parts of nano-calcium carbonate and 10 to 20 parts of 3% phosphoric acid solution; the modified nano-calcium carbonate comprises the following raw materials in parts by mass: 4 to 6 parts of phosphoric acid-modified nano-calcium carbonate, 30 to 40 parts of 70 to 80% ethanol aqueous solution, 3 to 5 parts of 3-aminopropyltriethoxysilane and 2 to 3 parts of mercaptopropyltrimethoxysilane.